Ruminal and morphometric parameters of rumen and intestine in lambs fed guava (Psidium guajava L.) agroindustrial waste - Nobre,Priscila Torres (2020)
ABSTRACT The objective of this study was to evaluate the effect of guava agroindustrial waste (GAW) on ruminal parameters (pH, N-NH3, and microbial protein), volatile fatty acid (VFA), and morphometry of the rumen and intestine of sheep. A total of forty Santa Inês sheep (120 days old and 21.3±2.62 kg) were used. The animals were fed diets with 0, 7.5, 15, 22.5, and 30% inclusion of GAW. The pH, ammonia nitrogen, microbial protein, and VFA were evaluated in the ruminal fluid, alongside the morphometric characteristics of the rumen and intestine. The inclusion of GAW linearly increased fasting and postprandial pH, N-NH3 only showed a quadratic effect for fasting animal, whereas MP presented a quadratic effect for pre- and post-prandial animals. There was a quadratic effect for papilla width, with a maximum value of 393.33 μm at the level of 34.43% GAW in the diet. The papilla absorption area showed a linear effect, in which increasing levels of GAW in the diet had a smaller area of papillae absorption. The inclusion of GAW in the diet of Santa Inês sheep favored pH neutrality, reduced N-NH3 and ruminal MP concentrations, decreased the thickness of the rumen muscular layer, and increased the intestinal mucosa, favoring greater absorption of nutrients.